2018
DOI: 10.1002/adfm.201801394
|View full text |Cite|
|
Sign up to set email alerts
|

Fluorescent Organic Glass with Unique Optical and Mechanical Properties

Abstract: Conventional organic glasses such as molecular and polymeric glasses either lack processability or have ill-defined properties. Here, a novel organic glass is reported having well-defined fluorescent properties and high compatibility with various fabrication processes. The fluorescent organic glass (FOG) is synthesized by simply heating benzyl alcohol with a small amount of aqueous sulfuric acid. Owing to its outstanding optical properties, FOG is placed beyond the domain of conventional organic glasses in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Based on the Rayleigh scattering principle, it is known that smaller grain size (in nano level) can favorably reduce the scattering of the incident light (Figure 2g). Due to the crystallization behavior of (ETP) 2 MnBr 4 nanocrystals during the molten-quenching process, the resultant solidified medium from molten ETPBr and MnBr 2 mixture exhibited high transmittance in the wavelength range from 500 to 800 nm (>80%) (Figure 2h), [29] implying its great applicable perspectives in high-resolution X-ray imaging applications, as will be discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Rayleigh scattering principle, it is known that smaller grain size (in nano level) can favorably reduce the scattering of the incident light (Figure 2g). Due to the crystallization behavior of (ETP) 2 MnBr 4 nanocrystals during the molten-quenching process, the resultant solidified medium from molten ETPBr and MnBr 2 mixture exhibited high transmittance in the wavelength range from 500 to 800 nm (>80%) (Figure 2h), [29] implying its great applicable perspectives in high-resolution X-ray imaging applications, as will be discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that MH is amorphous (Supplementary Figs. 13,14), because only broad peaks at around 10 and 20 degrees were observed from its powder X-ray diffraction spectra 50 . Meanwhile, no peaks were found in the small angle X-ray scattering spectra (Supplementary Fig.…”
Section: The Interior Structure Of Supramolecular Glassmentioning
confidence: 99%
“…The development of artificial glass has been regarded as a significant milestone in the long history of transparent materials. With advancements in polymer science, organic glass, which originates from covalently linked polymers, has become indispensable for various applications [13][14][15] . Currently, inorganic and organic materials are two classes of the most extensively used transparent materials 16 .…”
mentioning
confidence: 99%
“…For example, amorphous solid dispersions, drug formulations composed of active pharmaceutical ingredients dispersed in an amorphous glassy matrix, have been shown to improve important variables of biological drug efficacy such as transport and dissolution. The value of the glassy state has also been exploited for incorporating liquid crystal mesogens into low molecular weight matrices for information storage materials . Randomly organized, glassy materials have also been used as host matrices to lock in chromophore guests in the design of optoelectronic materials. More recently, small molecules have been designed for well-defined fluorescent glasses, nonlinear optics, charge transporting devices, and radioluminescence . Related to fulvenes of interest to this work, it has been reported that 1,2,3,4-tetraphenyl substituted fulvenes exhibited T g ’s of over 100 °C, and correlate with the nature of the 6-substituent (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…15 Randomly organized, glassy materials have also been used as host matrices to lock in chromophore guests in the design of optoelectronic materials. 16−18 More recently, small molecules have been designed for well-defined fluorescent glasses, 19 nonlinear optics, 20 charge transporting devices, 21 and radioluminescence. 22 Related to fulvenes of interest to this work, it has been reported that 1,2,3,4-tetraphenyl substituted fulvenes exhibited T g 's of over 100 °C, and correlate with the nature of the 6-substituent (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%